Eruption, transport mechanisms and deposition of Paleogene ignimbrites, southwestern North Patagonian Massif, Argentina - Salani, Flavia (2023)
The Paleocene-Eocene Catán Lil Ignimbrite (CLI) is one of the few occurrences within the explosive acid volcanism of this age in the extra-Andean region of the North Patagonian Massif. It represents a small-scale explosive eruption covering an area of 214 km2, with an estimated volume of 1.27 km3 and consisting of three weakly-to densely welded cooling units. The maximum thickness of this sequence is 90 m. Its basal unit is the best preserved, and has allowed a lithofacial analysis that reveals different aspects of the eruption and the emplacement mode of the Catán Lil pyroclastic flows. The CLI ignimbrites are generally massive, poorly sorted, matrix-supported deposits (tuff and lapilli tuff) resulting from dense pyroclastic currents (PDCs). They are composed mainly of juvenile fragments, scarce lithoclasts and crystalloclasts, being a product of a purely magmatic fragmentation occurred at a shallow level. A pyroclastic fountaining eruptive model is interpreted, resulting from the collapse of a low eruptive column, and a rapid and high-temperature emplacement. The CLI PDCs generally respond to slow moving pyroclastic flows with low erosive energy. The morphology and stratigraphy indicate radial emissions with thicknesses decreasing towards the periphery that become evident in Central-South ignimbrites. These PDCs flowed over a planar terrain, giving rise to most of the CLI deposits (South-Central area and North- East). The Northwestern ignimbrites are deposits in the interior (south and middle part) of the Catán Lil creek, forming thick deposits within the latter valley and thin, veneer-like deposits over the flanking Lipetrén granitoids. In the North- East region, the ignimbrites show stratigraphic relationships that suggest that the PDCs would slightly postdate those of the South-Central area. The Catán Lil Ignimbrites represent the most eastern exposures of the Paleocene-Eocene Pilcaniyeu Belt, differing from the latter in that it lacks a conspicuous lava facies, and by the unimodal character and the tectonic signature of the Catán Lil sequence.